Respuesta :
Hello,
P(x)=x^3-7x^2-18x+42
P(-3)=(-3)^3-7*(-3)²-18*(-3)+42=-27-63+54+42=6
If we do the division:
x^3-7x^2-18x+52=(x+3)(x²-10x+12) +6
Remainder=6
P(x)=x^3-7x^2-18x+42
P(-3)=(-3)^3-7*(-3)²-18*(-3)+42=-27-63+54+42=6
If we do the division:
x^3-7x^2-18x+52=(x+3)(x²-10x+12) +6
Remainder=6
Answer:
[tex]\text{The remainder is 6 when }x^3-7x^2-18x+42\text{ is divided by (x + 3)}[/tex]
Step-by-step explanation:
[tex]\text{Given the polynomial }x^3-7x^2-18x+42[/tex]
we have to find the remainder when above polynomial is divided by (x+3)
[tex]P(x)=x^3-7x^2-18x+42[/tex]
By remainder theorem,
[tex]P(3)=(-3)^3-7(-3)^2-18(-3)+42[/tex]
[tex]P(3)=-27-63+54+42[/tex]
[tex]P(x)=6[/tex]
Hence, the remainder is 6